CATABOLISM OF ECONOMIC SPACES OF SABILILLAH MOSQUE MALANG AND ITS ROLE IN COMMUNITY ECONOMIC EMPOWERMENT - Rahma Sandhi Prahara (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The catabolism that exists in the mosque's economic space is also caused by the reaction of complex compounds (mosques) into simpler compounds (the economic and even social spaces that are formed show more specific functions) with the help of developments over time and existing needs. The research methodology used is qualitative with a case study approach. The results of this research are that the catabolism process of mosque economic spaces experiences 5 phases. Starting from phase 1 to 4 then the fifth phase is that the social fund institution space creates another new space after the cooperative, namely lazis so that it becomes 1) mosque room, 2) REMAS room, 4) mosque cooperation, 5) Lazis. The catabolism process of economic spaces in mosques gives rise to empowerment which can be classified in the social and economic fields. Of course, there are also supporters and obstacles to this process, including human resources. Keywords: Catabolism, Mosque Economy, Community Empowerment